Perspective of Teachers on Their Competencies for Inclusive Education - Nimante, Dita; Kokare, Maija (Acta Paedagogica Vilnensia, 2022)
The purpose of this paper is to share findings about teachers’ perceived competencies for inclusion based on data gathered from 1590 (N = 1590) teachers representing 69 mainstream schools of Riga municipality using a survey. In answering the research questions on how teachers perceive themselves, if they have the necessary competencies for implementation of inclusive education, and what is missing, the results showed teachers self-reporting that despite the lack of specific qualification for inclusive education, they have the necessary competencies for inclusion. Teachers indicated that they have a slightly higher level of general competence; however, there is room for improvement in both general and specific competencies for inclusive education. Two of the most important specific competencies for inclusive education that they lack are the “implementation of an inclusive and supportive learning process for everybody by differentiating and adapting the curriculum” and a “timely identification of pupils’ difficulties in the learning process.” The findings reveal the challenges, problems, and limitations that would arise in providing high quality inclusive education to meet the needs of all learners. Despite the fact that teachers perceive that they have certain competencies for inclusive education, the majority of teachers do not feel comfortable and confident in practice in the inclusive classroom. Answers to the other research question revealed a connection between teachers’ age, teaching experience, education, and teachers’ perception of general competencies for inclusive education. A connection was revealed between teachers’ age, teaching experience, and teachers’ perception of specific competencies for inclusive education. Based on the results, suggestions for further research and implications for practice are discussed.
Keywords: inclusion; competencies; mainstream teachers,; Riga municipality